Mothers of Misery : Child Abandonment in Russia - Ransel, David L. (Book collections on Project MUSE., 1988)
At the height of its operation in the second half of the nineteenth century, the central foundling home in Moscow was receiving 17,000 children each year. The home dispatched most to wet nurses and foster care in the countryside, where at any one time it supervised over 40,000 children in Moscow province and six adjoining provinces. Established by Empress Catherine II in the middle of the eighteenth century, the two central foundling homes (the other was in St. Petersburg) were intended to deal humanely with the growing problems of abandonment and infanticide and to serve as social laboratories for educating artisans and craftspeople. David Ransel explores the creation and management of these institutions, shows how they functioned as a point of contact between educated society and the village, and compares them to the European foundling care programs on which they were modeled. "There were two central foundling homes in Russia, one in Moscow, one in St. Petersburg. ... [In this book] no significant aspect of their history is left untouched, and many issues are described and analyzed in rich detail. ... the book becomes, in part, a history of rural Russia over a one-hundred-fifty-year period, or, more accurately, of the provincial hinterlands of the two capitals. ... The interaction between city and countryside turns out to be much more than a clich in this fascinating study."--Reginald E. Zelnik, American Historical ReviewOriginally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905